An Improved Optimization Model of Internet Charging Scheme in Multi Service Networks - Fitri Maya Puspita; Kamaruzzaman Seman; Bachok M.Taib; Zurina Shafii (Institute of Advanced Engineering and Science, 2012)
This paper will analyze new improved charging scheme with base price, quality premium and QoS networks involved. Sain and Herpers [5] already attempted to obtain revenue maximization by creating charging scheme of internet. The plan is attempted to solve multiple service networks scheme as an optimization model to obtain revenue maximization using our improved model based on [2] and [5]. The results show that improved model can be solved optimally using optimization tool to achieve better revenue maximization. DOI: http://dx.doi.org/10.11591/telkomnika.v10i3.623